The Joint Effects of Hubris, Growth Aspirations, and Entrepreneurial Phases for Innovative Behavior - Poblete, Carlos (Frontiers in Psychology, 2022)
Innovation is often seen as a crucial ingredient for a venture to grow, however, high business failure rates in entrepreneurship suggest that innovations are often driven by entrepreneurs blinded by overconfidence. Thus, anticipating when and why entrepreneurs would be motivated to innovate is a fundamental component for entrepreneurial success. Using a large sample obtained from population surveys conducted in 77 countries, this study analyzes what variables are significantly associated with innovative behaviors. The present research tests a model proposing that the joint effects of hubris, growth aspirations, and the length of entrepreneurial experience have a crucial impact on innovative outcomes. This study found that hubris among entrepreneurs is significantly related to their growth aspirations and that ambition, in turn, is positively related to innovative behaviors. In addition, results evidenced that both of these relationships are moderated by the length of entrepreneurial experience. These findings help to understand the need to wise up amateur entrepreneurs before innovative endeavors.